Mixed convection boundary layer flow on a vertical surface in a porous medium saturated by a nanofluid with suction or injection - Mat Yasin, Mohd Hafizi; Md. Arifin, Norihan; Nazar, Roslinda; Ismail, Fudziah; Pop, Ioan (Science Publications, 2013)
An analysis of the steady mixed convection boundary layer flow past a vertical permeable surface embedded in a porous medium saturated by a nanofluid is performed in this study. Numerical solutions of the similarity equations are obtained using the shooting method. Three types of metallic or nonmetallic nanoparticles, namely Copper (Cu), Alumina (Al2O3) and Titania (TiO2) are considered by using a water-based fluid to investigate the effect of the solid volume fraction or nanoparticle volume fraction parameter ψ of the nanofluid. The numerical results of the skin friction coefficient and the velocity profiles are presented and discussed. It is found that the imposition of suction is to increase the velocity profiles and to delay the separation of boundary layer, while the injection parameter decreases the velocity profiles. On the other hand, the range of solutions for the injection case is largest for Al2O3 nanoparticles and smallest for Cu nanoparticles.